Kritikan Terhadap Rasulullah Dan Al-Quran: Analisis Karya Non-Muslim Zaman Umawiyyah Dan Abbasiyyah - Ahmad Sanusi Azmi; Mohd Yusuf Ismail; Zulhilmi Mohamed Nor; Amiruddin Mohd Sobali (Universiti Sains Islam Malaysia, 2024)
The contact between Muslim conquerors and the residents of subdued provinces created the grounds for each religious party to launch a defensive mode. Defending religion and its dignity could be considered as a legitimate task of each individual citizen. This phenomenon is well-recognised within the period of Umawiyyah and Abbasiyyah. Each religious authority endeavoured to serve their religion in their own best interests. One of the earliest religious reactions records alarm at the advance of the Arabs and its religious motivation. This is engraved in the Greek apologetic work entitled Doctrina Jacobi in which the document did not avoid discussing the veracity of his prophethood. Thus the present study aims to explore the earliest non Muslim sources that produced critical theological discourse on Muhammad and the Quran. It will indeed employed a qualitative analysis in which descriptive approach and source-critical analysis will be utilised. The study in its finding argued that there are various patterns of criticism on Muhammad and the Quran that eventually form a concrete fundamental foundation for the later generation in their study on the Prophet and the Quran.